Islamic Fintech: A Solution for Financial Problem - Dwi Marlina Wijayanti; Fachmi Pachlevi Yandra (Global Review of Islamic Economics and Business, 2021)
This research aims to examine the role of Islamic fintech in solving users’ financial problem. Furthermore, technology acceptance model (TAM) construct is used to explain individual acceptance on Islamic fintech. This research use self-administered survey including 185 Islamic fintech users spread all over Indonesia. This research provides empirical insights about user satisfaction on Islamic fintech product. It show that almost predictors have significant positive effect on user satisfaction. The TAM’s construct can predict and assess user perceptions on the use of new technologies or products. Furthermore, Islamic fintech makes it easy for users to solve their financial problems. This research proves that Islamic fintech product can be an option in solving financial problem without worrying about halal status.